Russian-language publication activity of medical researchers in during the COVID-19 pandemic: “post-COVID-19 syndrome” - O. T. Kim; O. M. Drapkina; Yu. V. Rodionova (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To study the dynamics and pattern of publications in Russian on post-COVID-19 syndrome (PCS) in order to assess the completeness of information and identify medical specialties with its most active investigation in Russia.Material and methods. The search for publications was carried out in the database of the largest digital scientific library in Russia Elibrary.ru from February 1, 2021 to February 1, 2022. The study included publicly available medical publications on the consequences of coronavirus disease 2019 (COVID-19) in Russian. Publications were classified according to subject matter, study design, and evidence hierarchy. The data obtained is reflected using integers, percentages and graphs.Results. The study included 478 publications, of which 196 (41%) presented data from original studies, while 269 (56,3%) reflected the results of existing sources. Expert community documents accounted for 2,7%. In terms of study design, most of original studies described case series (37,2%) and individual case reports (22,4%). Casecontrol studies accounted for 20,4%, cross-sectional studies — 8,7%, prospective cohort studies — 3,6%, randomized clinical trials — 1,5%, and systematic reviews — 1%. In addition, 5,1% of publications were devoted to preclinical studies, mathematical models and various methodological aspects. By topic, the largest number of publications noted cardiovascular (12,2%) and neurological manifestations of PCS (12,2%). Furthermore, 23,5% of publications described the course of PCS in specific groups of patients, particular issues of COVID-19 consequences, and healthcare management problems. We also revealed that 11,7% of publications were devoted to general rehabilitation, 71% — to imaging diagnostics, 5,6% — to herd immunity to the Severe Acute Respiratory Syndrome CoronaVirus 2 (SARSCoV-2), and 5,6% — to PCS features in children. The smallest number of publications considered mental (5,1%), gastroenterological (4,6%), pharmacological (4,6%), rheumatological (4%) and pulmonological aspects of PCS.Conclusion. The dynamics and pattern of publications on COVID-19 in Russian are generally consistent with global trends and reflect the natural consequences of the pandemic. This analysis of publications on PCS showed that the most in-demand specializations in this filed are cardiology, neurology, and rehabilitation.